DENOTATION, CONNOTATION, AND MYTH THROUGH VERBAL AND NON-VERBAL SIGNS ON REPRESENTATION OF IDENTITY IN THE BIG SIX PREMIERE LEAGUE CLUB LOGOS - Arif Lutfi Rohmani; Suyatman, Ujang; Sakinah, R. Myrna Nur (Esteem Journal of English Education Study Programme, 2025)
This study investigates the verbal and non-verbal elements within the logos of the "Big Six" Premier League clubs, aiming to uncover their denotative, connotative, and mythological meanings, and how these aspects represent identity. Using a qualitative descriptive approach based on Roland Barthes' semiotic framework, the research draws data from official club websites and documented literature. The analysis reveals that logos embody club identities through denotation, connotation, and myth, reflecting the historical, cultural, and social values associated with the clubs and their respective cities. Key components such as colors, symbols, and text, which are distinctive to each logo, play a significant role. This study contributes to the fields of cultural studies, semiotics, sports branding, and identity representation in visual communication and design. By exploring the semiotic depth of football logos, it bridges cultural semiotics and sports branding, uncovering often-overlooked narratives and enhancing both academic and fan perspectives on logo symbolism.